Prevalence, Cell Tropism, and Clinical Impact of Human Parvovirus Persistence in Adenomatous, Cancerous, Inflamed, and Healthy Intestinal Mucosa - Xu, Man; Leskinen, Katarzyna; Gritti, Tommaso; Groma, Valerija; Arola, Johanna; Lepistö, Anna; Sipponen, Taina; Saavalainen, Päivi; Söderlund-Venermo, Maria (Frontiers in Microbiology, 2022)
Parvoviruses are single-stranded DNA viruses, infecting many animals from insects to humans. Human parvovirus B19 (B19V) causes erythema infectiosum, arthropathy, anemia, and fetal death, and human bocavirus (HBoV) 1 causes respiratory tract infections, while HBoV2-4 are enteric. Parvoviral genomes can persist in diverse non-permissive tissues after acute infection, but the host-cell tropism and the impact of their tissue persistence are poorly studied. We searched for parvoviral DNA in a total of 427 intestinal biopsy specimens, as paired disease-affected and healthy mucosa, obtained from 130 patients with malignancy, ulcerative colitis (UC), or adenomas, and in similar intestinal segments from 55 healthy subjects. Only 3 (1.6%) individuals exhibited intestinal HBoV DNA (one each of HBoV1, 2, and 3). Conversely, B19V DNA persisted frequently in the intestine, with 50, 47, 31, and 27% detection rates in the patients with malignancy, UC, or adenomas, and in the healthy subjects, respectively. Intra-individually, B19V DNA persisted significantly more often in the healthy intestinal segments than in the inflamed colons of UC patients. The highest loads of B19V DNA were seen in the ileum and colon specimens of two healthy individuals. With dual RNAscope in situ hybridization and immunohistochemistry assays, we located the B19V persistence sites of these intestines in mucosal B cells of lymphoid follicles and vascular endothelial cells. Viral messenger RNA transcription remained, however, undetected. RNA sequencing (RNA-seq) identified 272 differentially expressed cellular genes between B19V DNA-positive and -negative healthy ileum biopsy specimens. Pathway enrichment analysis revealed that B19V persistence activated the intestinal cell viability and inhibited apoptosis. Lifelong B19V DNA persistence thus modulates host gene expression, which may lead to clinical outcomes.